16SrDNA-Based Detection Technology in Patients with Chronic Pharyngitis to Analyze the Distribution Characteristics of Pharyngeal Bacteria. (11th March 2022) - Shen, Yage; Liu, Chunhan; Luo, Jiao; Wang, Jianchao; Zhang, Di
Abstract : In order to analyze the distribution characteristics of pharyngeal bacteria in patients with chronic pharyngitis (CP) by 16SrDNA-based detection technology, a prospective study is conducted to collect pharyngeal secretion samples from patients diagnosed with CP who are admitted to the Otorhinolaryngology Department of The Third People's Hospital of Shenzhen from May 2021 to September 2021. Among them, 11 cases are chronic simple pharyngitis (CSP), 11 cases are chronic hypertrophic pharyngitis (CHP), and 8 cases are healthy subjects. All samples are detected by the 16SrDNA technique and analyzed by bioinformatics. 55724.64 ± 1772.80, 53697.73 ± 2252.19, and 55177.5 ± 1661.80 optimized sequences are obtained by 16SrDNA sequencing. The α diversity analysis of pharyngeal microflora showed that the abundance index SOBS of pharyngeal microflora is upregulated in patients with CHP compared with normal controls (NC), but the diversity index of pharyngeal bacteria in the three groups is not significantly changed, indicating that the abundance of pharyngeal bacteria in the CHP group is increased. The β diversity analysis of pharyngeal microflora showed that the three groups are similar in structure and composition, and there is no significant statistical difference. The structural difference analysis of pharyngeal flora combined with LEfSe difference analysis showed that at the phylum level, the relative abundance of Spirochaetes and Synergistetes in the CHP group is significantly higher than that in the CSP group. At the genus level, the relative abundance of opportunistic pathogens such as Selenomonas and Campylobacter increased significantly in the CSP group. The relative abundance of Escherichia, Mycoplasma, and Porphyromonas are significantly increased in the CHP group. The abundance of beneficial symbiotic bacteria decreased significantly in patients with CP. The pharyngitis of patients with CP is characterized by an increase in the abundance of pharyngitis, changes in the structure of pharyngitis, a decline in the symbiotic beneficial bacteria, and an increase in the content of opportunistic pathogens, which may be closely related to the onset and development of CP.